Analisis Pengetahuan Lingkungan dan Sikap Peduli Lingkungan terhadap Ekosistem Sungai Berbasis Kearifan Lokal Lubuk Larangan di Desa Tambangan Jae Kecamatan Tambangan Kabupaten Madina - Hidayah, Nur; Syarifuddin, Syarifuddin; Gultom, Tumiur (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
This research aims to: Find out the level of students and communities environmental knowledge towards river ecosystem based local wisdom (in)* lubuk larangan (part of the river which the fishes cannot be taken until the certain time)* basedon the level of education; Determine the level of environmental knowledge of students and communities towards river ecosystem based local wisdom lubuk larangan. The research used a quantitative descriptive research. The research sample as many as 158 students and 50 communities who live in Tambangan village Tambangan District, Madina Regency. The instrument used in this research was a questionnaire. Data analysis technique used Friedman-test. The final conclusion of the research: The level of education and location of the school influenced the level of knowledge about the environment of students based on local wisdom lubuk larangan basedon the level of education. The average of adultâs knowledge was higher than High School, Junior High and Elementary School students.